Stimulation of Monocytes by Placental Microparticles Involves Toll-Like Receptors and Nuclear Factor Kappa-Light-Chain-Enhancer of Activated B Cells - Joerger-Messerli, Marianne Simone; Hoesli, Irene Mathilde; Rusterholz, Corinne; Lapaire, Olav (Frontiers in Immunology, 2014)
Human pregnancy is accompanied by a mild systemic inflammatory response, which includes the activation of monocytes circulating in maternal blood. This response is exaggerated in preeclampsia, a placental-dependent disorder specific to human pregnancies. We and others showed that placental syncytiotrophoblast membrane microparticles (STBM) generated in vitro from normal placentas stimulated peripheral blood monocytes, which suggest a contribution of STBM to the systemic maternal inflammation. Here, we analyzed the inflammatory potential of STBM prepared from preeclamptic placentas on primary monocytes and investigated the mode of action in vitro. STBM generated in vitro by placental villous explants of normal or preeclamptic placentas were co-incubated with human peripheral blood monocytes. In some cases, inhibitors of specific cellular functions or signaling pathways were used. The analysis of the monocytic response was performed by flow cytometry, enzyme-linked immunoassays, real-time PCR, and fluorescence microscopy. STBM derived from preeclamptic placentas up-regulated the cell surface expression of CD54, and stimulated the secretion of the pro-inflammatory interleukin (IL)-6 and IL-8 in a similar, dose-dependent manner as did STBM prepared from normal placentas. STBM bound to the cell surface of monocytes, but phagocytosis was not necessary for activation. STBM-induced cytokine secretion was impaired in the presence of inhibitors of toll-like receptor (TLR) signaling or when nuclear factor kappa-light-chain-enhancer of activated B cells (NF-κB) activation was blocked. Our results suggest that the inflammatory reaction in monocytes may be initiated by the interaction of STBM with TLRs, which in turn signal through NF-κB to mediate the transcription of genes coding for pro-inflammatory factors.